Batik Besurek Sebagai Sumber Ide Perancangan Motif Untuk Busana Wanita Ready To Wear - Nabila Bafaqih, Sofia Nabila; Darwoto, Darwoto (Pusat Penerbitan LPPM ISI Bali, 2022)
The Besurek Batik motif comes from the city of Bengkulu, and the word “Besurek” means “letter writing” or just “writing”. One of the most distinguished features of Besurek Batik is its similarity to Arabic calligraphy letters, but in this case, it’s meaningless and more of a decorative form. The background of this design is to introduce Besurek Batik motifs to the public by designing women’s ready-to-wear clothing through a different technique, namely digital printing. This design project is also aimed to answer the question/problem of how to design motifs with Besurek Batik as the source of ideas for women’s ready-to-wear clothing by using a digital printing technique. The design method that is used as a reference to address this problem is the Collin Clipson method which states that there are five stages in the process of designing, namely problem identification, design analysis, creative process, production process, and marketing distribution. In this project, the data was collected by observation, interviews, visual studies, and product comparison studies. The technique used in this design is the digital printing technique, which makes the production process faster and cheaper compared to other printing techniques. The result of this design is women’s ready-to-wear clothing. Ready-to-wear clothing is simple and comfortable clothing that is suited for daily activities. Not just that, women’s ready-to-wear clothing can also be seen as a medium to popularize the Besurek Batik motif. Everyone who wears ready-to-wear clothing with Besurek Batik motifs is expected to inspire others in getting to know the motif.